VD_FINDINFO HC / 2012 / 524 vom 24. Juli 2012 - VD Tribunal cantonal (2012)
AUTORITÉ PARENTALE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, EXPERTISE | 133 CC, 276 al. 2 CC, 285 CC, 240 CPC, 243 CPC, 291 CPC, 308 CPC (CH), 404 al. 1 CPC (CH)